The Size of Flypaper Effect in Decentralizing Indonesia - Tengku Munawar Chalil (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2018)
This study explores the flypaper effect in Indonesia using a spatial approach. Covering data from 2000-2014, the paper shows that grants stimulate overspending by local governments even though spatial interdependence is carefully treated. The elasticity of lump-sum grants to expenditure is stronger than the elasticity of matching grants. Further, the elasticity of lump-sum grant is greater on routine expenditure, which shows the overdependency of local governments to lump-sum grant. The over - dependency phenomenon has not changed a lot even after a major change of lump-sum grant formulation being applied by the 2004 decentralization law package.